Preston Sturges : the last years of Hollywood's first writer-director - Smedley, Nick; Sturges, Tom (Intellect, 2019)
Few directors of the 1930s and '40s were as distinctive and popular as Preston Sturges, whose whipsmart comedies have entertained audiences for decades. With a foreword by Peter Bogdanovich and endorsements from Francis Ford Coppola, Ron Shelton, and James L. Brooks, this book offers a new critical appreciation of Sturges's whole oeuvre, closing with a detailed study of his life, developed from new primary sources, from 1949 until his death in 1959. Nick Smedley details the many unfinished projects of Sturges's last decade, including films, plays, TV series, and his autobiography. Drawing on diaries, sketchbooks, correspondence, unpublished screenplays, and more, Smedley presents Sturges's final years in more detail than we've ever had, showing a master still at work--even if very little of that work ultimately made it to the screen